STUDENTS’ PERCEPTIONS : THE USE OF TELEGRAM APPLICATION AS AN E-LEARNING TOOL IN ENGLISH CLASS - Maya Yuliana; Diah Kurniati; Muh Syafei (Universitas Muria Kudus, 2023)
This study aims to determine students' perceptions of using the Telegram Application as a tool in learning in English class and also to find out what benefits they get when using the Telegram Application. In this study, the researcher used a qualitative descriptive method. Researchers used a questionnaire to determine the perceptions of students who were given to and interviews, namely to gain deep information about the questionnaire and to find out what benefits they got. There were 65 students who filled out the questionnaire and 26 students who had been interviewed. The results showed that the students' Perceptions towards the use of Telegram Application as an e-learning tool have positive perceptions. Moreover it was also revealed that the students get benefits when studying through the Telegram Application, they get many benefits. From the results, the majority of students agree that through Telegram students can make it easier to get material, make it easier for students to understand the material, as well as the many benefits they get from learning through the Telegram Application.